Short-term use of “ECMELLA” in the context of fulminant eosinophilic myocarditis with cardiogenic shock - Bohné, Mintje (BMC Cardiovasc Disord, 2020)
BACKGROUND: Eosinophilic myocarditis (EM) is a rare form of myocarditis. Clinical presentation is various, includes cardiogenic shock and can often be fatal. Diagnosis is based on myocardial eosinophilic infiltration in endomyocardial biopsy. Mechanical circulatory support (MCS) is often required in patients suffering from severe cardiogenic shock. Among the available MCS options the “ECMELLA” concept, a combination of left ventricular venting by Impella® device and extracorporeal life support (ECLS) is possibly able to provide the necessary time frame for diagnostics and initiation of anti-inflammatory medication in patients with fulminant myocarditis. CASE PRESENTATION: We report a case of a 38‐year‐old woman who was presented to us in severe cardiogenic shock, quickly requiring hemodynamic support by an Impella CP® device. Further dramatic hemodynamic deterioration accompanied by multi-organ dysfunction required escalation of MCS via ECLS as veno‐arterial extracorporeal membrane oxygenation (VA-ECMO). After histopathological diagnosis of EM, our patient was put on immunosuppressive therapy with prednisolone. Recovery of both right and left ventricular function allowed explanation of VA-ECMO on day 4 and further hemodynamic improvement allowed removal of the Impella® device on day 9. The patient was discharged after 7 weeks with fully restored cardiac function and in a good neurological state. CONCLUSIONS: In severe cardiac shock due to fulminant EM the ECMELLA concept as bridge-to-recovery seems to be a valid option to provide the required time for diagnostics and specific therapy.